Appraisal resources and national image: a case study on Chinese Foreign Ministry spokespersons’ responses about COVID-19 - Qi, Yuan Liu; Lay, Hoon Ang; Waheed, Moniza; Mohd Kasim, Zalina (Academy Publication, 2022)
The national image of a country is becoming increasingly important as the soft power of a country, which can be realised by diplomacy and various types of diplomatic discourses. Therefore, this study attempts to analyse, via the responses of Chinese Foreign Ministry Spokespersons to questions about COVID-19, how national images are constructed. It adopts the Appraisal Theory proposed by Martin and White and focuses on one of its systems: attitude. Attitude resources are evaluative languages that express feelings, opinions and judgements which are quite contributive to the building of a national image and they are very abundant in the the foreign spokespersons’ responses. This study uses Atlas.ti as the tool to collect and code appraisal resources in order to observe the overall features of attitude, including word frequency and collocation. Together with this tool, the Critical Discourse Analysis approach is also used to analyse the meaning of attitude resources as well as the political and diplomatic contexts. The study finds that different attitude resources can contribute to the formation of different components of national images according to specific political events or international relationships, and this gives more insights into the construction of China’s national image during the pandemic.